The Change of Left Ventricular Function in Rats with Subclinical Hypothyroid and the Effects of Thyroxine Replacement - Xuedi Chen; Cuixia Gao; Ningning Gong; Yu Wang; Limin Tian (International Journal of Endocrinology)
Objective. The main purpose of this study was to explore the relationships between serca2a, Ryr2, adipokines, and the left ventricular function in the subclinical hypothyroidism with different TSH levels and to determine the impact of L-T4 treatment on these indexes. Methods. Sixty-five male Wistar rats were randomly divided into five groups: control group; sHT A, B, and C group; and sHT + T4 group. The sHT rats were induced by methimazole (MMI), and the sHT + T4 rats were administered with L-T4 treatment after 8 weeks of MMI administration. Serum TT4, TSH, APN, chemerin, and TNF-α were detected by radioimmunoassay kits and ELISA kits; left ventricular function was measured by PowerLab system via subclavian artery catheter. The expression of Serca2a, Ryr2, APN, chemerin, and TNF-α were detected by RT-PCR, Western blot, and immunohistochemistry. Results. The sHT groups had significantly higher TSH, chemerin, and TNF-α and lower Serca2a, Ryr2, and APN. The left ventricular pressure and heart rate in sHT groups were significantly lower in control and sHT + T4 group. Histopathological examination revealed the pathological changes in the sHT rats’ heart. L-T4 administration reduced TSH level and improved left ventricular function. Conclusions. TSH can impair left ventricular function by regulating several factors, and L-T4 treatment ameliorates it in sHT rats.